Finding a catalog: generating analytical catalog records from well-structured digital texts - Mimno, David; Jones, Alison; Crane, Gregory (Proceedings of the 5th ACM/IEEE Joint Conference on Digital Libraries : Denver, CO, USA, June 7-11, 2005 : digital libraries, cyberinfrastructure for research and education, 2005)
One of the criticisms library users often make of catalogs is that they rarely include information below the bibliographic level. It is generally impossible to search a catalog for the titles and subjects of particular chapters or volumes. There has been no way to add this information to catalog records without exponentially increasing the workload of catalogers. At the same time, well-structured full-text XML transcriptions of printed works are becoming increasingly available. This paper describes how existing investments in full text digitization and structural markup combined with current named-entity extraction technology can efficiently generate the detailed level of catalog data that users want, at no significant additional cost. This system is demonstrated on an existing digital collection within the Perseus Digital Library.